2020
DOI: 10.3390/biology9080214
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermostability and Enzymatic Activity of cel6A Variants from Thermobifida fusca by Empirical Domain Engineering

Abstract: Cellulases are a set of lignocellulolytic enzymes, capable of producing eco-friendly low-cost renewable bioethanol. However, low stability and hydrolytic activity limit their wide-scale applicability at the industrial scale. In this work, we report the domain engineering of endoglucanase (Cel6A) of Thermobifida fusca to improve their catalytic activity and thermal stability. Later, enzymatic activity and thermostability of the most efficient variant named as Cel6A.CBC was analyzed by molecular dynamics simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Their research suggests that cellulose hydrolysis can be improved for larger bioethanol outputs. Ali et al [ 94 ], also found that uncovering Cel6A variations from Thermobifida fusca utilizing protein domain engineering and molecular dynamics investigations improved their enzymatic activity. Computer-based different microbial cellulase enzyme is given in Figure 2 .…”
Section: Molecular Modelingmentioning
confidence: 99%
“…Their research suggests that cellulose hydrolysis can be improved for larger bioethanol outputs. Ali et al [ 94 ], also found that uncovering Cel6A variations from Thermobifida fusca utilizing protein domain engineering and molecular dynamics investigations improved their enzymatic activity. Computer-based different microbial cellulase enzyme is given in Figure 2 .…”
Section: Molecular Modelingmentioning
confidence: 99%
“…The readily available T. fusca genome sequence reveals that it has the capacity to express many enzymes useful for hydrolyzing biomass, including numerous cellulases, xylanases, and carbohydrate transporters for sugar uptake ( Lykidis et al, 2007 ). Many of these thermally stable enzymes have been heterologously expressed in alternative microbial hosts and analyzed for their applicability to biomass conversion ( Ghangas and Wilson, 1987 ; Ali et al, 2015 ; Klinger et al, 2015 ; Saini et al, 2015 ; Zhao et al, 2015 ; Setter-Lamed et al, 2017 ; Yan and Fong, 2018 ; Ali et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%